Saving energy and water in tourist accommodation: A systematic literature review (1987–2015). (3rd February 2017) - Warren, Christopher; Becken, Susanne
Abstract: Current climate change policy and sustainable tourism goals require tourist accommodation to make substantial resource savings. This integrated energy and water systematic literature review analysed 110 key papers that contribute to understanding savings potentials and new opportunities. Findings identify substantial gaps that suggest that there is insufficient guidance on how to reduce resources and progress sustainability‐oriented innovation. Benchmarks for energy and water were compiled alongside potential resource savings. Findings indicate opportunities for stronger collaborative effort particularly in areas of nonhotel accommodation, water savings, and guest behaviour, which are almost unstudied. A research framework to advance energy and water saving innovations is proposed.